Dietary Lipid Modulation of Intestinal Serotonin in Ballan Wrasse (Labrus bergylta)—In Vitro Analyses - Etayo, Angela; Le, Hoang T. M. D.; Araujo, Pedro; Lie, Kai K.; Sæle, Øystein (Frontiers in Endocrinology, 2021)
Serotonin (5-HT) is pivotal in the complex regulation of gut motility and consequent digestion of nutrients via multiple receptors. We investigated the serotonergic system in an agastric fish species, the ballan wrasse (Labrus bergylta) as it represents a unique model for intestinal function. Here we present evidence of the presence of enterochromaffin cells (EC cells) in the gut of ballan wrasse comprising transcriptomic data on EC markers like adra2a, trpa1, adgrg4, lmxa1, spack1, serpina10, as well as the localization of 5-HT and mRNA of the rate limiting enzyme; tryptophan hydroxylase (tph1) in the gut epithelium. Second, we examined the effects of dietary marine lipids on the enteric serotonergic system in this stomach-less teleost by administrating a hydrolysed lipid bolus in ex vivo guts in an organ bath system. Modulation of the mRNA expression from the tryptophan hydroxylase tph1 (EC cells isoform), tph2 (neural isoform), and other genes involved in the serotonergic machinery were tracked. Our results showed no evidence to confirm that the dietary lipid meal did boost the production of 5-HT within the EC cells as mRNA tph1 was weakly regulated postprandially. However, dietary lipid seemed to upregulate the post-prandial expression of tph2 found in the serotonergic neurons. 5-HT in the intestinal tissue increased 3 hours after “exposure” of lipids, as was observed in the mRNA expression of tph2. This suggest that serotonergic neurons and not EC cells are responsible for the substantial increment of 5-HT after a lipid-reach “meal” in ballan wrasse. Cells expressing tph1 were identified in the gut epithelium, characteristic for EC cells. However, Tph1 positive cells were also present in the lamina propria. Characterization of these cells together with their implications in the serotonergic system will contribute to broad the scarce knowledge of the serotonergic system across teleosts.